Plumarius brasiliensis Penteado-Dias and Scatolini, 2003 (Hymenoptera, Plumariidae): notes on its temporal variation in the Cerrado and new distribution records in Brazil - Perioto, Nelson Wanderley; Lara, Rogéria Inês Rosa; Fernandes, Daniell Rodrigo Rodrigues; Ferreira, André da Silva; Martins, André Luis (Papéis Avulsos de Zoologia, 2024)
This study is focused on the parasitic wasp Plumarius brasiliensis Penteado-Dias & Scatolini, 2003 (Hymenoptera, Plumariidae). Data assembled from 12 consecutive months of systematic samplings at Parque Nacional Grande Sertão Veredas, in Minas Gerais, Brazil, indicate that the largest populations of P. brasiliensis occur there in the dry season, with few specimens collected in the rainy season, which may indicate that this group or its hosts have a seasonal pattern. This species is also reported for the first time in areas of Cerrado, in the states of Minas Gerais and Maranhão; in the core of Caatinga, in the state of Rio Grande do Norte; and in transition zone between Caatinga and Cerrado, in the state of Piauí, Brazil. The new distributional records in areas of Cerrado and Caatinga/Cerrado ecotone represent a significant increase in the geographic range of P. brasiliensis that can be present in about 35% of the Brazilian territory. Additionally, we provide digital images and diagnosis of this species and a map with the geographical distribution of the studied species based on the new records and literature data.